2015
DOI: 10.15302/j-fem-2015004
|View full text |Cite
|
Sign up to set email alerts
|

Applying an Integrated Systems Perspective to the Management of Engineering Projects

Abstract: Engineering projects can be subject to significant complexity, which may result in a number of issues and challenges that need to be addressed throughout the project life-cycle. Traditionally projects have been viewed according to the so called "iron triangle," i. e., achievement of project milestones according to schedule, cost and quality targets. While these targets are fundamentally important to the performance of engineering projects, it is possible to view projects on a systemic level in order to allow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The task of the construction phase is to combine this structured system in an effective manner (Halfawy and Froese, 2007). Philbin (2015) proposed an integrated system, which included the process, technology, resource, knowledge, culture, and impact of technology. Liu et al (2014) identified certain critical success factors for innovation in the construction phase from the perspective of integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The task of the construction phase is to combine this structured system in an effective manner (Halfawy and Froese, 2007). Philbin (2015) proposed an integrated system, which included the process, technology, resource, knowledge, culture, and impact of technology. Liu et al (2014) identified certain critical success factors for innovation in the construction phase from the perspective of integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is commonly accepted that good research and development practices are essential for growing and well positioned large enterprises in the manufacturing market, commonly having dozens or hundreds of projects. The development of competitive new products is likely the most important task that allows a manufacturing enterprise surveillance within a competitive environment [1,2]; such NPD projects can positively impact in the company competitive position allowing a better efficiency in the product management, and/or the generation of social benefits [3]. Hence, for the growth of enterprises under stiff competition, good New Product Development (NPD) projects are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional reductionist focuses on the isolated components of a system and frequently overlooks critical interactions across individual components. System theory emphasizes the integration of individual systems to achieve a common system goal (Davies and Mackenzie, 2014;Philbin, 2015). General methods of construction management cannot be simply applied to mega-projects.…”
mentioning
confidence: 99%